Challenges among individuals with visual impairment in an institution of higher learning in Malaysia - Cheong, L.S.; Abdullah, H.S.L.; Yusop, F.D.; Muhamad, A.S.; Tsuey, C.S.; Wei, C.S. (2012)

(untitled)
Students with disabilities face physical. social. and emotional barriers in their post secondary education. Some barriers may include obstruction in the environment, lack of awareness in the university community and peer participation. This article explores the experiences and challenges faced by visually impaired students in a public university in Malaysia. The article delves into the feelings and aspirations ofthe students as they study in the University. It gives an insight into the lives of the students with disabilities and how they cope throughout their stay in the university.